Topical administration of broccoli flower (brassica oleraceae l. Var italica plenck) extract cream 10% prevented increased of melanin in UVB exposed guinea pig (cavia porcellus) - Tambor Tiur Marlina; Wimpie Pangkahila; AAGP Wiraguna (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Skin aging is primarily caused by increased free radicals and decreased cellular anti-oxidant system in keratinocyte. Broccoli flower contains several important antioxidant molecules that can inhibit aging process of the skin. Therefore, the aim of this research is to prove the effectivity of administration broccoli flower extract cream on inhibiting the elevation of melanin level on guinea pig (Cavia porcellus) exposed with UV-B. Methods: An animal experiment with post-test only controls group design was conducted using 36 guinea pigs which were divided into 2 groups. The control group was treated with placebo cream while treatment group was treated with 10% broccoli flower extract cream. All groups were exposed with UV-B with dose at 390 mJ/cm2 for 2 weeks and biopsy was taken to examine the level of melanin. Results: The results showed that the average amount of melanin expression in the control group (P0) was 21.48 ± 1.48% while it was 1.32 ± 0.85% in treatment group (P1). Independent T-test analysis showed that the difference was statistically significant (t = 33.95; p = 0.001). Conclusion: It can be concluded that the topical administration of broccoli flower extract cream prevented increase in skin melanin in UV-B exposed guinea pig.